Effect of diluted dielectric medium on spark energy in green EDM process using TGRA approach. (20th November 2019) - Muthuramalingam, T.
Abstract: In the present situation, it is very important for modifying any manufacturing process into eco friendly process to reduce the environmental pollutants and hazardous substances. In electrical discharge machining process, the dielectric breakdown of insulating medium causes on liberating the toxic gases from the machining zone. In the present study, a research endeavor was performed to analyze the influence of process parameters with normal tap water mixed deionized water as insulating medium. It has been inferred that proposed dielectric medium can provide considerable machinability while machining titanium alloy. The optimum combination has also been found using Taguchi Grey-relational approach to achieve better multiple response parameters in the proposed eco friendly electrical discharge machining process. However, the material removal mechanism with proposed dielectric medium in EDM process may be affected due to stochastic and higher electrical conductivity of the insulating medium. Graphical abstract: Image 1015726 Highlights: The proposed dielectric medium can provide considerable machinability in EDM. Discharge current and duty factor can highly contribute on spark energy. The normal water affects the electrical permittivity of insulating medium in EDM. The optimal combination of process parameters has been found.